2019
DOI: 10.24940/theijhss/2019/v7/i9/hs1909-077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress on Employee Productivity within the Hospitality Industry in Ghana Using Selected Cafeterias

Abstract: In today's competitive global environment, employee productivity is an essential element of a company's success. Employee productivity can be significantly hindered by high levels of stress experienced in the work environment. Stress is a universal phenomenon and persons from nearly every walk of life have to face stress. Employers today are critically analyzing the stress management issues that contribute to lower job performance of employees. The main aim of the study is to examine the impact of stress and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although work stress is a phenomenon that emerges under the influence of various factors, it also has negative consequences for employees and businesses [14,15]. Previous studies have shown that work stress levels can affect employees' well-being [5], affective and normative commitment, job satisfaction [16], job performance [17], productivity [18], work alienation [19], depression, cardiovascular disease, cancer risks [20], turnover intentions [21], and burnout levels [22]. This study focuses on the work-related burnout problem, which is negatively affected by work stress, from among the aforementioned variables.…”
Section: Introductionmentioning
confidence: 99%
“…Although work stress is a phenomenon that emerges under the influence of various factors, it also has negative consequences for employees and businesses [14,15]. Previous studies have shown that work stress levels can affect employees' well-being [5], affective and normative commitment, job satisfaction [16], job performance [17], productivity [18], work alienation [19], depression, cardiovascular disease, cancer risks [20], turnover intentions [21], and burnout levels [22]. This study focuses on the work-related burnout problem, which is negatively affected by work stress, from among the aforementioned variables.…”
Section: Introductionmentioning
confidence: 99%